The Use of New Media Technology in Families and Its Impact on Intimacy - Hana Rizquna Nabela; Puji Rianto (Asian Journal of Media and Communication, 2020)
This study aims to find out how the presence of new media technology affects the communication intimacy between children and parents. Applying a qualitative approach, the empirical data for this study were collected through interviews, observations, documents, and audiovisual materials in two smartphone user families in Java, Indonesia. This study finds that the presence of new media technology has affected the intimacy of family, both in the aspects of communication, trust, and alienation. The use of smartphones can widen the communication distance between parents and children.Â Keywords:Â new media technology, family intimacy, communication, trust, alienation.